On the relationship between some abilities and tendencies to choose certain studies - Mikšytė , G. (Psichologija, 1973)
Analyzing the quantitative and qualitative data after testing the 10th grade students propencities to certain field of study, it was determined that tendencies to choose certain studies is related to the ability to determine the relationships in plane surface, spatial thought images, and abilities to determine quantitative relationships. It was found that the tendency to choose certain studies is related to certain developmental features of specific abilities.